Emily Gray - A thesis submitted in partial fulfilment of the requirements of the degree of Doctor of Clinical Psychology (DClinPsych) - Gray, E (2021)
Critical Review of the Literature: How effective are family therapies for the treatment of substance abuse in young people? A systematic review and meta-analysis: